PENGELOMPOKAN KABUPATEN/KOTA DI JAWA TIMUR BERDASARKAN INDIKATOR PENDIDIKAN TAHUN 2013 MENGGUNAKAN ANALISIS HIERARCHIAL CLUSTER - Elok Fitriani Rafikasari (LP2M IAIN Tulungagung, 2016)
National development efforts in improving quality of education especially in East Java are to create and to apply the police that in accordance with education level in each district. Making policy is aimed to achieve awareness and capability to contend especially in education field. In the context of assisting the manufacture of the policy needs to be done a grouping of the education level of community in the district in East Java to understand the extent of the development of the spread of the level of schooling. The purpose of this studyis to find groups of districts in East Java have characteristic together in thefield of education. While the method of analysis is that are used hierarchical clusters. From this analysis obtained two groups where the first group a number of 29 the districts which have the level of education higher than the second group with 9 of districts.Kata Kunci: Clustering, Level Pendidikan, Analisis Hierarchical Cluster